Use of Anopheles salivary biomarker to assess seasonal variation of human exposure to Anopheles bites in children living near rubber and oil palm cultivations in Côte d'Ivoire. (May 2019) - Sadia-Kacou, Cécile Agnimou Malanfoua; Yobo, Céline Mabot; Adja, Maurice Akré; Sagna, André Barembaye; Ndille, Emmanuel Elanga; Poinsignon, Anne; Tano, Yao; Koudou, Benjamin Guibehi; Remoue, Franck
Abstract: Environmental changes related to agricultural practices and activities can impact malaria transmission. In the objective to evaluate this impact on the human-vector contact, the level of human exposure to Anopheles vector bites was assess by an immuno-epidemiological indicator based on the assessment of the human IgG antibody response to the Anopheles gambiae gSG6-P1 salivary peptide, previously validated as a pertinent biomarker. Two cross-sectional surveys were carried out in the dry and rainy season in three villages with intensive agricultural plantations (N'Zikro with rubber cultivation, Ehania-V5 and Ehania-V1 with palm oil exploitation) and in a control village without plantations (Ayébo). Overall, 775 blood samples were collected in filter papers from children aged 1 to 14 years-old for immunological analysis by ELISA. The IgG levels to the gSG6-P1 salivary peptide significantly differed between studied villages both in the dry and the rainy seasons ( P  < 0.0001) and were higher in agricultural villages compared to the control area. In particular, the level of specific IgG in Ehania-V5, located in the heart of palm oil plantations, was higher compared to other agricultural villages. Interestingly, the level of specific IgG levels classically increased between the dry and the rainy season in the control village (P < 0.0001) whereas it remained high in the dry season as observed in the rainy season in agricultural villages. The present study indicated that rubber and oil palm plantations could maintain a high level of human exposure to Anopheles bites during both the dry and rainy seasons. These agricultural activities could therefore represent a permanent factor of malaria transmission risk.